Development of Metacognitive Self Assessment for Junior High School Students on Materials Interaction of Living Things and Their Environment - Chaetsunnajah, Chaetsunnajah; Dewi, Novi Ratna (Universitas Negeri Semarang, 2023)
Based on the 2013 curriculum and Regulation of the Ministry of Education and Culture number 20 of 2016 concerning Achievement of Graduation Standards, graduates must not only be equipped with factual, conceptual, procedural knowledge but also metacognitive knowledge related to the field of knowledge, which is science. Metacognition can be measured by certain evaluation tools, so the instruments used in the learning assessment are oriented towards metacognition abilities. One of the characteristics of metacognitive assessment is that it involves students in their self-assessment process. Self-assessment is a habit of thinking about the relationship between metacognition and reflection. Metacognitive self-assessment is a metacognitive assessment instrument developed in this research, consisting 20 questions of metacognitive ability test and reflection journal as a self-assessment. This study aims to test the feasibility, analyze the characteristics of the product and determine the metacognitive profile of students. The results of data analysis showed that the Metacognitive Self Assessment product was very feasible with an average percentage obtained of 92.78% according to material experts, 86.43% according to evaluation experts, and the feasibility of readability data based on student responses of 83.59%. Metacognition profiles data based on their level are also supported by the results of reflection journals as a form of self-assessment that students have been able to carry out the process of reflection and evaluation of learning and what they are doing.